Implementation Of Islamic Business Ethics In Increasing Customer Loyalty (Study At Noorshofea Store) - Amalia Putri Geta Sahani; Muhammad Ersya Faraby (Jurnal Ekonomi, 2024)
The research delves into the realm of Islamic business ethics, particularly focusing on their application within the context of Noorshofea Store. This research is significant due to the increasing importance placed on ethical conduct in business, particularly within Islamic frameworks. By understanding and analyzing the practices of Noorshofea Store through the lens of Islamic business ethics, the research aims to provide insights into how such principles can enhance customer loyalty. Various efforts have been made to increase the application of Islamic business ethics at the Noorshofea Store so that customer loyalty continues to increase. Additionally, the identification of barriers and proposed solutions contributes to the broader understanding of challenges in implementing Islamic business ethics in contemporary business environments. Through qualitative field research methods like interviews, observation, and documentation analysis, this study seeks to offer a comprehensive understanding of the subject matter, thereby contributing to both academic scholarship and practical applications in business settings.